Centchroman a better alternative for hormonal oral contraceptive pills - MAJOR(DR) V K YADAVMD; DR.PARAG SHARMA.MD; DR. RAJ SHARMA.PHD; DR.JAYANTHI YADAV.MD (International Journal of Pharma and Bio Sciences, 2011)
Centchroman (Ormeloxifene) is a non steroidal Oral Contraceptive Pill (OCP), popular in India as once weekly pill being issued free of cost through Primary Health Centers as an initiative from the government and also commercially available. It has several advantages over steroidal OCPs and thus it is logical to offer this OCP to women all over the world. This commentary tries to highlight on this issue.